Prevalence and Intensity of Gastrointestinal Helminthes in Glyphoglossus molossus and Kaloula pulchra from Din Chi Subdistrict, Kammaung District, Kalasin Province - เลาห์ประเสริฐ, คมศร; ภักดีณรงค์, นพคุณ (KKU Science Journal, 2017)
Thirty four blunt-headed burrowing frog (Glyphoglossus molossus) and ten banded bullfrog (Kaloula pulchra) were excavated and collected during a dry season (October 2015 and January 2016) at Din Chi Subdistrict, Kammaung District, Kalasin Province to study prevalence and intensity of gastrointestinal helminthes in these frogs. The results showed that 26 of 34 G. molossus were infected by helminthes. The prevalence was 76.47% (26/34), including 2 nematodes, i.e., Aplectana sp. and Amphibiophilus sp. and 1 acanthocephalan, that is, Acanthocephalus sp. Almost helminths were found at intestine with the prevalence as 11.76 %, 70.59%, and 2.94%, respectively. 8 of 10 K. pulchra were infected by helminthes. The prevalence of K. pulchra was 80% (8/10), including 3 nematodes, i.e., Aplectana sp., Amphibiophilus sp., and Camallanus sp. Almost helminthes were found at intestine with the prevalence as 10.00%, 40.00% and 30.00%, respectively. The data of this research could be used as a prevention guideline and helminth infections control planning tool from bullfrogs to humans and animals.